Kewenangan Notaris/PPAT Melaksanakan Jasa Escrow Pembayaran Bea Perolehan Hak Atas Tanah dan Bangunan - Kadek Krisnanda Pandi Putri; I Wayan Novy Purwanto (Fakultas Hukum, Universitas Warmadewa, 2024)
Revenue from taxation, constituting the primary financial resource of a nation, mandates compliance from all taxpayers. Among the requisite fiscal impositions, the BPHTB Tax applies to transactions involving the acquisition of land and building rights. In this context, the Notary/PPAT, who serves as a public functionary in creating authentic transactional deeds, is frequently empowered by the involved parties to both hold tax payment funds in trust and to facilitate the payment of BPHTB Tax upon due. This function is recognized as Escrow Services. The focal legal question of this study concerns both the regulatory vacuum surrounding the authority granted to Notary/PPAT to administer BPHTB Tax payment via Escrow Services, and the nature of the accountability that must be assumed by Notary/PPAT when such services are exploited for personal gain. The approach employed in this scholarly endeavor constitutes a normative legal examination, concentrating primarily on the scrutiny of statutes. The principal subject of investigation is the norms and regulations stipulated within these legislative documents. The acquisition of legal information is executed through an analysis of documents or by conducting literature reviews. Subsequently, the amassed legal data undergoes analysis via a qualitative methodology. This study underscores the critical need for precise stipulations and restrictions concerning the Authority vested in Notary/PPAT. This regulation is perceived as possessing significant urgency in bestowing legal certainty upon all involved entities. It is articulated within Article 15 of the UUJNP that the Notary/PPAT lacks the authority to execute Escrow Services. Moreover, in an expression of accountability, Notary/PPAT who exploit the authority associated with Escrow Services dispensed by the parties will face criminal and administrative penalties.